Fertilizer potential of biochar and ryegrass productivity in metal-contaminated soil - Antonangelo, Joao Arthur; Bigatao Souza, Joao Luis; Zhang, Hailin (Frontiers in Plant Science, 2025)
IntroductionResponse to fertilization with biochar in contaminated soils for forage crops lacks comprehensive understanding. This study delves into the role of biochar in enhancing soil pH and phosphorus (P) and potassium (K) availability for ryegrass (Lolium perenne) in clay and silt loam metal-contaminated soils.MethodsTwo pot experiments were conducted using switchgrass-derived biochar (SGB) and poultry litter-derived biochar (PLB) with varying biochar application rates: one without plants and the other with ryegrass.ResultsResults demonstrated a significant rise in soil pH with increasing biochar rates, particularly notable for the PLB experiment with plants, attributed to PLB’s superior buffer capacity. PLB significantly improved ryegrass productivity, evident in germination percentage, plant population, and biomass, especially at a 0.5-1% biochar application rate. However, excessive biochar application (2-4%) hindered plant growth.DiscussionPLB at 1% application sufficed to barely surpass critical P and K thresholds for optimal ryegrass production, whereas SGB fell short of meeting these thresholds, highlighting the importance of biochar feedstock selection. While biochar shows promise for metal remediation and nutrient enhancement, caution is advised against excessive application, considering potential nutrient contamination risks based on feedstock variations.